Understanding Public Attitudes to Hate: Developing and Testing a U.K. Version of the Hate Crime Beliefs Scale - Bacon, Alison M. (Journal of interpersonal violence, 2021)
Against the backdrop of an increase in reported hate crimes, we present the development of a U.K.-focussed instrument designed to evaluate the nature of public beliefs about hate crime, legislation, offenders and victims. In Study 1, 438 participants completed an Anglicized version of the Hate Crime Beliefs Scale (HCBS). Factor analyses revealed three subfactors: Denial (high scores represent a denial of hate crime severity and need for legislation), Compassion (high score reflect compassion toward victims and affected communities) and Sentencing (higher scores reflect more punitive attitudes). In Study 2 (N = 134) we show that scores on Denial are positively associated with those on Right-Wing Authoritarianism (RWA) and Social Dominance Orientation (SDO), ideologies known to be associated with prejudice. Compassion was negatively associated with these ideologies. Mediation analyses showed that Big Five personality traits Openness to Experience and Conscientiousness predicted Denial and Compassion via RWA, whereas Agreeableness and Openness predicted scores via SDO, consistent with a dual-process motivation model of hate crime beliefs. Results are discussed in terms of the nature of hate crime beliefs and the importance of understanding public attitudes which may support undesirable social norms and influence jury decision making in trials of hate related offenses.